Structured Reporting in Sleep Medicine - Katharina Bahr-Hamm; Haralampos Gouveris; Barbara Leggewie; Sven Becker; Friederike Bärhold; Benjamin Philipp Ernst (Diagnostics)
Background/Objectives: Somnological findings are often written as free texts, supported by questionnaires. The quality and structure of free-text reports (FTRs) vary between examiners and specialties, depending on the individual level of expertise and experience in sleep medicine. This study aimed to compare the quality of free-text reports (FTRs) and structured reports (SRs) from somnological consultations in otolaryngology for patients assessed for obstructive sleep apnea (OSA). Methods: This study compared free-text reports (FTRs) and structured reports (SRs) from 50 patients with suspected OSA, including medical history, clinical examination findings, and medical letters, all prepared by six examiners with similar experience levels. A web-based approach was used to develop a standardized template for structured somnological reporting. The completeness and time required for both FTRs and SRs were evaluated, and a questionnaire was administered to assess user satisfaction with each reporting method. Results: The completeness scores of SRs were significantly higher than those of FTRs (88% vs. 54.2%, p < 0.001). The mean time to complete an SR was significantly shorter than that for FTRs (10.2 vs. 16.8 min, p < 0.001). SRs had significantly higher user satisfaction compared to FTRs (VAS 8.3 vs. 2.2, p < 0.001). Conclusions: Compared to FTRs, SRs for OSA patients are more comprehensive and faster. The use of SR is more satisfactory for examiners and supports the learning effect.